Formation of attitudes of teaching computer science in secondary school - Dagienė, Valentina (Information & Media, 1997)
The article is devoted to the activities of the expert groups of Computer Science that are teaching and working at the Ministry of Education and Science. The first expert group of Computer Science teaching was established in autumn 1990 and is renewed every school year. The main functions of the expert group are: a) to give an incentive to writing textbooks or other methodical material; b) to review and approbate manuscripts of teaching materials; c) to consider teaching curricula, standards, and other documents concerning school activity; d) to prepare an outline and tasks of Computer Science examination; e) to take care of teacher training. Changes in teaching Computer Science methodology and curricula are described. The first Computer Science national course, teacher-training problems, the preparation of textbooks, and curricula and standards of Computer Science are discussed.